Antimicrobial Effect of Blue Light Cure and Antibiotics Combination on Serratia Merasences Isolated from Apical Root Canal - Hadeel Mizher Younis (Journal of Global Pharma Technology, 2016)
Objectives: To evaluate the phototoxic influence on the serratia merasences potentially by the antimicrobial effect of blue light cure and antibiotics combination. Methods: The growth of serratia merasences samples has been found after being exposed to blue light cure with and without the existence of antibiotics (metronidazole, doxycycline) on the brain heart infusion broth for (15, 20, 35, 60, and 70 sec) and then cultured on mitis media to determine its effect. Results: The present study manifested that the bacterial growth was reduced after the exposure to blue light for (60 and 70 sec) in the absence of antibiotics. While, the combination of blue light laser for (35 sec) with the concentration of antibiotics doxycycline and metronidazole (64 Mg/ml, 128 Mg/ml), respectively has yielded 95% growth inhibition. The result revealed the direct antimicrobial influence of light cure and antibiotics metronidazole, doxycycline) combination on the serratia merrasences isolations. Conclusions: The influence of an antibacterial synergistic between antibiotics and blue light used has been noticed. The blue light cure in combination with antibiotics (metronidazole, doxycycline) applied to the tooth infection could be a substitution to observe as an extra minimum treatment of antibacterial.Keyword: Blue light cure, Antibiotics, Microorganisms.